Polisi Amerika Terhadap Perkembangan Politik Islam di Mesir - Mohd Nasir, Badlihisham (Jurnal Usuluddin, 2002)
It is commonly known that there was unsettled conflict between the West and the Islamic world. The conflict which was manifested in the form of debated throughout many decades became a serious discussion particularly after the tragedy of September 11, 2001. Islam which was largely been associated with radicalism and terrorism becomes the world first enemy. Hence, many actions have been taken to eradicate the resurgence of political Islam in the Muslim world. Some of them involves the establishing of certain particular policy by the states in the Middle East. The essay which is based on the chapter of the book entitled America and Political Islam: Clash of Culture or Clash of Interests’ written by Fawaz A. Gerges will introduce the process of establishing American policy in Egypt, the anchor of the Islamic political movement for the Muslim world of today.